Factors affecting the adoption of diseaseresistant plantain and banana (Musa spp.) hybrids in Nigeria - Aitchedji, C.C.; Tenkouano, A.; Coulibaly, O. (2010)
The study assesses the level of adoption of hybrid cultivars of plantain andbanana (Musa spp.), promoted through plantain promotion projects based onfarmer-to-farmer diffusion and extension events, and determines the factorsaffecting their adoption and dissemination in four plantain and banana growingareas of Nigeria. Data have been analyzed with an econometric Logit model. Theresults indicate that the farmer capacity to choose and use planting materials andrelated production techniques has been significantly improved by training programsover a period of four years. Farmer awareness has been increased through fielddays, demonstration plots, farmer exchange visits and a platform for sharinginformation on hybrids and associated techniques. Reasons reported by farmers toadopt the hybrids include high yields, resistance to black leaf streak, taste/goodcooking quality, and access to planting materials due to the rapid multiplicationtechnique deployed by the project. Farmers, who participated in on-farm trials,demonstration plots, field days and/or other training programs on hybrids andassociated technologies during the five last years, adopted the hybrid cultivarsbecause of their direct participation and contact with breeders and other projectpartners. The project’s collaboration with the national extension system for theorganization of annual training programs with pioneer farmers on hybrid cultivarsand associated technologies has highly contributed to the large and effectivedissemination and adoption of plantain and banana hybrids by small farmers.